Memupuk Jiwa Entrepreneur Sejak Dini: Integrasi Konsep Kewirausahaan dalam Pembelajaran di SD - Andi Dewi Riang Tati; Muhammad Irfan; Romansyah Sahabuddin; Muh. Faisal (Mathematics Education Study Program, 2025)
This study aims to examine relevant literature on the integration of entrepreneurial concepts in learning at the elementary school level. The study uses the library research method to explore entrepreneurial concepts and their integration into learning through data analysis from various sources of literature. The research steps include identifying keywords, selecting relevant literature, and conducting content analysis to categorize information based on key themes such as entrepreneurial concepts and integration strategies. The findings are synthesized into a theoretical framework that emphasizes the importance of fostering entrepreneurial spirit from an early age and provides guidance for educators in designing innovative learning approaches. Entrepreneurial education not only teaches business skills but also builds character traits such as independence, creativity, and problem-solving abilities through real-world experiences and entrepreneurial projects. With a supportive learning environment, students can develop confidence, social skills, and a sense of responsibility, helping them become innovative and socially beneficial individuals. Project-based learning (PjBL) is an effective method for teaching entrepreneurship in the class by encouraging creativity and critical thinking through hands-on experiences such as market simulations and business competitions.